Redlining, Concentrated Disadvantage, and Crime: The Effects of Discriminatory Government Policies on Urban Violent Crime - Powell, Richard (American journal of criminal justice, 2023)
Redlining and other discriminatory government policies enacted during the first half of the Twentieth Century have had long-lasting negative effects on neighborhoods, especially those inhabited by people of color. This study attempts to link the practice of redlining to current-day indicators of neighborhood concentrated disadvantage and violent crime using spatio-temporal data from Chicago. Specifically, the study seeks to determine whether redlining has been associated with increased levels of concentrated disadvantage since its implementation in the 1930s. In addition, it seeks to determine whether redlining was associated with violent crime, and if that association was mediated by redlining’s effect on concentrated disadvantage. The results indicate that redlining was associated with increases in both concentrated disadvantage and violent crime, and that redlining’s relationship with violent crime was, indeed, partially mediated by its relationship with concentrated disadvantage. The findings from this study suggest that to reduce violent crime in urban communities, we cannot simply rely on our current punitive criminal justice system. Instead, policies should focus on reducing concentrated disadvantage and racial isolation by helping economically strengthen severely disadvantaged neighborhoods and by increasing residential mobility for individuals currently living in those neighborhoods.